Rural Technology Development and Delivery RuTAG and Its Synergy with Other Initiatives - Saha, Subir Kumar; Ravi, M. R. (Design Science and Innovation, 2019)
This book comprises the proceedings of a rural technologies conference organised by the Rural Technology Action Group (RuTAG), which was conceptualized and initiated by Principal Scientific Adviser (PSA) to the Government of India R. Chidambaram in 2003-04. The book highlights case studies and research into providing science and technology interventions for the development of rural areas. Covering various aspects of research carried out in the area of rural technologies, it offers a valuable resource for researchers, professionals, and policymakers alike.